Physiological responses to self-induced burrowing and metabolic rate depression in the ocean quahog Arctica islandica - Strahl, Julia; Brey, Thomas; Philipp, Eva; Thorarinsdottir, G.; Fischer, Natalie; Weßels, Wiebke; Abele, Doris (Journal of Experimental Biology, 2011)
Arctica islandica is the longest-lived non-colonial animal found so far, and reaches individual ages of 150years in the German Bight (GB) and more than 350years around Iceland (IC). Frequent burrowing and physiological adjustments to low tissue oxygenation in the burrowed state are proposed to lower mitochondrial reactive oxygen species (ROS) formation. We investigated burrowing patterns and shell water partial pressure of oxygen (PO2) in experiments with live A. islandica. Furthermore, succinate accumulation and antioxidant defences were recorded in tissues of bivalves in the normoxic or metabolically downregulated state, as well as ROS formation in isolated gills exposed to normoxia, hypoxia and hypoxia/ reoxygenation. IC bivalves burrowed more frequently and deeper in winter than in summer under in situ conditions, and both IC and GB bivalves remained burrowed for between 1 and 6days in laboratory experiments. Shell water PO2 was <5kPa when bivalves were maintained in fully oxygenated seawater, and ventilation increased before animals entered the state of metabolic depression. Succinate did not accumulate upon spontaneous shell closure, although shell water PO2 was 0kPa for over 24h. A ROS burst was absent in isolated gills during hypoxia/reoxygenation, and antioxidant enzyme activities were not enhanced in metabolically depressed clams compared with normally respiring clams. Postponing the onset of anaerobiosis in the burrowed state and under hypoxic exposure presumably limits the need for elevated recovery respiration upon surfacing and oxidative stress during reoxygenation.